Return to work rate rises in the Sunshine State (Queensland, Australia). (12th November 2014) - Stratford, Sharon
Abstract : Measuring return to work outcomes after injury is in itself a challenge for most workers' compensation schemes. Increasing return to work rates is even more difficult. In Australia, the national return to work measure obtained via an annual survey of injured workers has not risen since its introduction in 1997/98. However, unlike most other Australian jurisdictions, Queensland, Australia's 'sunshine state', records return to work outcomes at the end of every time lost claim. More than this, Queensland has increased its overall return to work outcome in recent years from 90% to over 95%. A number of specific strategies were introduced to improve these return to work results. The presentation will outline these strategies which other jurisdictions and countries can hopefully learn from. In addition, WorkCover Queensland, the state's monopoly insurer outside self-insurers, has introduced further return to work measures it successfully uses both internally and externally.